Do We Fear God in Maintaining Scientific Journal Accountability? - Aji Dedi Mulawarman; Jordan Hotman Ekklesia Sitorus; Muhammad Ichsan (Yayasan Rumah Peneleh, 2022)
This study aims to explore aspects of transcendental accountability in the management of scientific accounting journals. Paradigma Nusantara was employed to analyse thoroughly the accountability activities of the manager of scientific accounting journals. This study found that a phenomenonof accountability manipulation by some scientific journal managers were apparent. They did so because of the publisher's discriminatory attitude. In addition, there is an increasing loss in the fear of God in managing journals. The article proposes to establish transcendental accountability to be applied in the management of scientific journals using Sunan Kalijaga’s Ilmu Kasampurnan